B Cell Immunity in Lung Transplant Rejection - Effector Mechanisms and Therapeutic Implications - Ohm, Birte; Jungraithmayr, Wolfgang (Frontiers in Immunology, 2022)
Alloimmune graft rejection remains the major hurdle in lung transplantation despite modern immunosuppressive treatment. As part of the alloreaction process, B cells are now increasingly recognized in graft rejection as modulators of alloimmunity and initiators of a donor-specific humoral response. In chronically rejected lung allografts, B cells contribute to the formation of tertiary lymphoid structures and promote local alloimmune responses. However, B cells are functionally heterogeneous and some subsets may promote alloimmune tolerance. The aim of this review is to describe the current understanding of B-cell-dependent mechanisms in pulmonary allograft rejection and to highlight ongoing and promising future strategies employing B cell-targeted therapies.